Neoaltar: An interactive multimedia day of the dead experience - Baquier Orozco, Rogelio; Barraza Castillo, Ramon Ivan; Husted Ramos, Silvia (2020)
Technology has permeated many aspects of human life, from everyday events, entertainment, learning environments, festivities, even solemn ceremonies; such is the case of the century-old Mexican tradition of Day of the Dead. Altars or offerings as they are sometimes called, are a central part of this celebration; whether they are small homemade shrines or big public installations, they are a narrative medium to tell the life-story and honor the memory of a beloved or important individual. This paper presents the creation of a traditional and technologically enhanced offering dubbed Neoaltar, from the identification and classification of narrative elements found in traditional altars, the proposal of an interactive multimedia interface based on a user experience model, and the construction, installation, live demonstration and evaluation of the altar. The exhibition of the offering was done during the most important and publicly open Day of the Dead event in the Mexican city of Juárez; as part of this study a survey was created, and information gathered from 120 users is analyzed and presented. The Neoaltar strives to tell the life story of the departed by introducing a non-linear interactive multimedia narrative while keeping with tradition by using a non-invasive approach to technology inclusion.